Best little monkeys in the world (The) - Standiford, Natalie (New York : Random House, 1987)
When their parents go out to a party, two little monkeys make mischief while their baby-sitter thinks they are being good.
Keywords: Monkeys-Fiction; Baby-sitters-Fiction; Behavior-Fiction